Design of a Web Based Accounting Editor. - Igwali, Micheal Jackson (Kabale University, 2023)
Starting at 2009, companies have had to report to the SEC financial statement using XBRL protocol. One of the main objectives was that comparison of data of companies over time will be automatic. Moreover, since every company should use the same taxonomy, comparison between companies would be easy. Unfortunately, companies are allowed to change and add to the basic taxonomy even between years; thereby, the comparability between Financial Statements (FS) of companies and between FS of the same company over the years are lost.